Immunohistochemical Assessment of Tumor Infiltrating T Cells and Serological Evaluation of Apoptotic Markers in Prostate Cancer Patients - Ifad Kerim AlShibly1 , Ammad Hasan Mahmood2 , Fouad Qasim Jubair Al-Zayadi3 , Hadeel Karbel4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
PCa is abnormal transformed growth in glandular prostate tissue of male reproductive system. Occasionally,it is slow growth, but some progressed rapidly. This corss-sectional study aims to evaluate the differences incounts of tumor infiltrating immune cells (CD3 & CD8), and serum soluble Fas and Fas ligand concentrationsbetween malignant and benign PCa. Total of (17) patients with PCa were included, their ages ranged from(38-88) years. The patients visited urological surgery unit in Hilla Teaching Hospital during the period(November 2018 to October 2019). The samples comprise biopsy for estimation of tumor infiltrating CD3& CD8 by IHC technique, and 3 mL of blood for sFas and sFasL evaluation by ELISA technique for eachpatient. The results showed the differences of CD3+ & CD8+ PILs counts between BPH and malignant PCaare non-significant (P value > 0.05), sFas concentrations of malignant PCa are significantly higher (P value< 0.05) than those of BPH, whereas no significant difference (P value > 0.05) in sFasL concentrations. Itwas concluded that prostate tumor type affects serum levels of sFas, but both CD3+ & CD8+ PILs rates andsFasL levels are not affected.